Psychological Dynamics of Drug Abuse in Women - Nadya Nur Rahmadhani; Ellyana Ilsan Eka Putri; Ade Septian (Philanthropy: Journal of Psychology, 2025)
Drug abuse among women is a growing phenomenon that affects psychological functioning, particularly for women who hold caregiving roles as mothers. However, studies on the psychological dynamics of women who abuse drugs are limited. This study aims to understand the psychological dynamics of women who use drugs, from initial exposure and use, to relapse, and the decision to stop. The research employed a qualitative method with a case study approach. Semi-structured interviews were conducted with two female correctional inmates who were convicted of narcotic offenses and met the study criteria. The analysis was conducted using the Interpretative Phenomenological Analysis approach. The findings indicate that the interaction of internal factors (self-regulation and motivation), emotional and spiritual conditions, and social factors influence psychological dynamics. These findings underscore the importance of gender-responsive and psychosocial rehabilitation approaches in understanding women’s drug abuse.